ChemInform Abstract: Self‐Assembly of 3d‐4f "Square‐in‐Square" Coordination Clusters Based on Substituted Diethanolamine Ligands. Issue 38 (September 2016) - Mameri, Samir; Mereacre, Valeriu
Abstract: Review: 51 refs.